Sound Absorption Characteristics of Pineapple Leaf/Epoxy Composite - ADHIKA, Damar Rastri; PRASETIYO, Iwan; NOERIMAN, Abiyoga; HIDAYAH, Nurul; WIDAYANI, S. (Archives of Acoustics, 2020)
Natural fibres are attractive as the raw material for developing sound absorber, as they are green, eco-friendly, and health friendly. In this paper, pineapple leaf fibre/epoxy composite is considered in sound absorber development where several values of mechanical pressures were introduced during the fabrication of absorber composite. The results show that the composite can absorb incoming sound wave, where sound absorption coefficients α _n > 0.5 are pronounced at mid and high frequencies. It is also found that 23.15 kN/m^2 mechanical pressure in composite fabrication is preferred, while higher pressure leads to solid panel rather than sound absorber so that the absorption capability reduces. To extend the absorption towards lower frequency, the composite absorber requires thickness higher than 3 cm, while a thinner absorber is only effective at 1 kHz and above. Additionally, it is confirmed that the Delany-Bazley formulation fails to predict associated absorption behavior of pineapple leaf fibre-based absorber. Meanwhile, a modified Delany-Bazley model discussed in this paper is more useful. It is expected that the model can assist further development of the pineapple leaf composite sound absorber.